PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF TERINTEGRASI PRAKTIKUM VIRTUAL PADA MATERI BUNYI - Novitasari, Lilik; Partono, Partono; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2023)
Abstract: This study aims to: 1) describe the design of interactive learning media integrated with virtual practicum, 2) find out the feasibility of the developed media, 3) find out the user's response to the practicality of using media in learning activities. This product development makes it easier for educators to convey material and makes it easier for students to understand the material. The product developed is in the form of interactive learning media integrated with virtual practicum on sound material. This research is research development or Research and Development using the ADDIE model. This research was conducted at SMPN 1 ANAK RATU AJI with class VIII students as research subjects. The instruments used in data collection were interview guide sheets and questionnaire sheets. Based on the results of this study, it can be interpreted that interactive learning media integrated with virtual practicum on sound material that has been developed is designed so that students can freely change menu choices or value variables as desired. The results of the acquisition of the average proportion of the validation value of media experts and material experts is 90.75% with a very feasible category and the results of the media practicality assessment by respondents obtained an average value of 88% with a very practical category, so it can be stated that interactive interactive learning media is integrated Virtual practicum on sound material can be used as a supporting medium for learning activities.